Analysis of Macroeconomic Indicators and It's Effect on Human Development Index (HDI) - Runtunuwu, Prince Charles Heston (Society, 2020)
This research aims to determine the effect of inflation, per capita income. The method used is a quantitative method with a descriptive approach. The data analysis technique uses multiple linear regression models, which are continued by the classical assumption test. This research uses secondary data, precisely ten years of time-series data from 2010-2019 obtained from the Central Bureau of Statistics, books, literature, the internet, records, and other sources related. The research sample consisted of 40 data taken per quarter, from 2010-2019. The analytical method used in this research is multiple linear regressions. The results showed that inflation had a negative and insignificant effect on Human Development Index (HDI). In contrast, per capita income and unemployment had a negative and significant effect on Human Development Index (HDI). Inflation, per capita income, and unemployment significantly affected the Human Development Index (HDI) in Ternate City. The independent variable’s determination (R Square) on the dependent variable is 0.836 or 83.6%. It means inflation, per capita income, and unemployment can affect the Human Development Index (HDI) in Ternate City at 83.6%, remaining 16.4% by other factors.